Idiopathic Pulmonary Fibrosis in Elderly Patients: Analysis of the INSIGHTS-IPF Observational Study - Leuschner, Gabriela; Klotsche, Jens; Kreuter, Michael; Prasse, Antje; Wirtz, Hubert; Pittrow, David; Frankenberger, Marion; Behr, Jürgen; Kneidinger, Nikolaus; , The INSIGHTS-IPF Registry Group; Andreas, Stefan; Bahmer, Thomas; et al. (Frontiers in Medicine, 2020)
Background: An association between idiopathic pulmonary fibrosis (IPF) and advancing age is suspected since IPF occurs primarily in patients over 60 years of age. Though, little is known about the disease in the elderly. The aim of this study was to characterize elderly IPF patients using data from the longitudinal, German-wide INSIGHTS-IPF registry. Methods: Patients were grouped into elderly (≥75 years) and nonelderly IPF (<75 years) at the time of enrollment into the study. Baseline clinical characteristics, comorbidities, health related quality of life (HRQoL), medical therapy and survival were compared between age groups. Effects of antifibrotic therapy on forced vital capacity (FVC) were analyzed over 24 months. Results: Of 1009 patients, 350 (34.7%) were ≥75 years old. Elderly IPF patients compared to younger patients had a higher number of comorbidities (3.6±2.5 vs. 2.8±2.3; p<0.001). The mean±SD EQ-5D score (0.64±0.21 vs. 0.69±0.21; p=0.005), and the overall WHO-5 score (13.1±5.9 vs. 14.3±6.0; p=0.015) were significantly lower while the UCSD-SOBQ (52.6±31.2 vs. 45.5±31.2; p=0.030) was significantly higher in elderly patients, indicating a more impaired HRQoL and more breathlessness. At baseline, 55.4% of elderly and 56.8% of nonelderly patients with IPF were treated with antifibrotic therapy (p=0.687). For FVC decline after initiation of antifibrotic therapy, there was neither a significant difference between age groups at the different time points over 24 months (beta: 0.41; 95%-CI: -0.98 to 1.81; p=0.563) nor over the whole course of time (beta: -0.05; 95%-CI: -0.20 to 0.09; p=0.478). All-cause mortality was higher in elderly patients (49.1% vs. 37.9%; HR 1.65; 95%-CI 1.36-2.00; p<0.001). Antifibrotic therapy was associated with improved survival in IPF patients, independent from age (<75 years: beta 0.76; 95%-CI: 0.59 to 0.99; p=0.049; ≥75 years: beta 0.71; 95%-CI: 0.51 to 0.98; p=0.043). Conclusion: In real life, a significant proportion of IPF patients are ≥75 years old, characterized by higher number of comorbidities and global reduced HRQoL. However, the effect of an antifibrotic therapy was similar between age groups and associated with a survival benefit emphasizing the importance for an early antifibrotic therapy in IPF, independent from age.